Incidence of Hypertension Among Children Treated With Adrenocorticotropic Hormone (ACTH) or Prednisolone for Infantile Spasms. (March 2020) - McGarry, Laurel; Messer, Ricka; Cree-Green, Melanie; Ray, Krista; Knupp, Kelly
Children with infantile spasms are often treated with hormonal therapies including adrenocorticotropic hormone (ACTH) and prednisolone. These have numerous systemic side effects including hypertension and, rarely, fatal cardiomyopathy; however, the incidence of these side effects has not been well described. This study aims to quantify the incidence and short-term sequelae of hypertension in this population. A retrospective chart review was performed at a single institution. Children 2 months to 2 years old with newly diagnosed infantile spasms treated from 2013 to 2017 were included. Variables collected included age, sex, etiology and treatment of infantile spasms, documented or missed diagnosis of hypertension, treatment of hypertension, echocardiogram results, referrals for hypertension, and persistence of hypertension 2 to 4 months after treatment. Analyses included descriptive statistics with percentiles, means, and medians. Differences between groups were assessed using Fisher exact tests. Hypertension occurred in 34/77 children (44%) during treatment with ACTH and 4/11 children (36%) during treatment with prednisolone. No child developed hypertension during treatment with nonhormonal therapies. The incidence of hypertension between ACTH and prednisolone groups was not significantly different ( P = .75). The incidence of hypertension was significantly higher in the ACTH and prednisolone groups compared to the nonhormonal group ( P < .001 for each). Sixteen children received echocardiograms, with no cases of cardiomyopathy. Two children had persistent hypertension at 2 months after discontinuation of hormonal therapy. Hypertension is a very common side effect of hormonal therapy for infantile spasms; however, few developed long-term hypertension and none developed cardiomyopathy. Further study is needed to determine the role of antihypertensive treatment for hormone-related hypertension.